Light-enhanced charge mobility in a molecular hole transporter - Snaith, H; Graetzel, M (2007)
We present an investigation into the charge transport through a molecular hole transporter. Under illumination, photoinduced charge transfer occurs from a sensitizer to the hole transporter. The increased hole density results in striking enhancements in film conductivity, up to 106, and charge carrier mobility, up to 103. Such enhancements in mobility at low charge densities have not previously been observed in molecular semiconductors, and demonstrate the importance of considering a charge-density dependent mobility in molecular semiconductors employed under photovoltaic operation. © 2007 The American Physical Society.